Fibrodysplasia ossificans progressiva: Review and research activities in Japan. Issue 1 (29th January 2020) - Haga, Nobuhiko; Nakashima, Yasuharu; Kitoh, Hiroshi; Kamizono, Junji; Katagiri, Takenobu; Saijo, Hideto; Tsukamoto, Sho; Shinoda, Yusuke; Sawada, Ryoko; Nakahara, Yasuo
Abstract: Fibrodysplasia ossificans progressiva (FOP) is a rare genetic skeletal disorder manifesting progressive heterotopic ossification (HO) and congenital malformation of the great toes. Since 2007, we have conducted research on FOP. Here, we review the findings on FOP published to date, including the results of our research. Epidemiological studies in Japan have indicated that FOP has nearly the same prevalence in Japan as in the rest of the world. Basic research on its pathoetiology has progressed rapidly since the identification of the causal gene in 2006. Clinical and radiological findings have been thoroughly researched, including early radiological signs, and diagnostic criteria were established, designating FOP as an intractable disease in Japan. In patients with FOP, the progression of HO is associated with numerous disabilities, often manifesting in vicious cycles that can lead to early mortality. Through cross‐sectional and short‐term longitudinal studies, we have explored patient education, quality of life, and activities of daily living among Japanese patients. The management of FOP requires education of patients and caregivers, the use of medications to settle inflammation and flare‐ups, instructions to ensure proper oral care, and other compensatory approaches that aid in rehabilitation. An avoidance of medical intervention, which may cause HO to progress, is also important. The advent of new drugs to prevent HO could have clinical benefit.